(3TQM fgL GdHdGZIs - (3CHhMGeO YRGdOjf YHO GdMejO Hf gHI Gddg Hf eMeO Hf GdMSjf Hf CHi GdMOjOs; (3GdTQja GdeQJVj , CHh GdbGSe,J (B436 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdYGOd hef cdGe dg Ydjg GdSdGe ai eYfi WdMI (B: (3hbO cfJ heG CgOO HGdMQH s
(3BNQgG (B:s
(3hdgPG GdeYfi Sei CHhSajGf Hf MQH EHf YfHSI, hSei SYjO Hf GdYGU EHf YfHSg hGdMeO ddg hMOg s
(3GdeLdO GdKGdK(B-(3bdjd GdGYLGes
(3YdjgG hba HJGQjN(B1065(3g`s
(3fSNI NGeSIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs